ANALYSIS OF PAYROLL ACCOUNTING INFORMATION SYSTEMS AT PT ALFA KREASI (WEEKEND INC) - Erni Wigati (International Journal Multidisciplinary Science, 2024)
This writing aims to determine the application of the Payroll Accounting Information System carried out at PT Alfa Kreasi (WEEKEND INC), as well as to analyze the implementation of the Internal Control System and provide proposals for the Payroll Accounting System to support the effectiveness and efficiency of the Internal Control System at PT Alfa Kreasi (WEEKEND INC ). The type of data used is qualitative data, data that explains a phenomenon based on things that generally contain words where the data obtained and which will be processed later is in the form of primary data, which is obtained directly through face-to-face interviews with the parties concerned. The analytical tools that the author uses in this research are data flow diagrams (DFD) and document flow charts (flowcharts). From the research that has been carried out, the author concludes that PT Alfa Kreasi (WEEKEND INC) implements a computerized payroll system seen in the recording process carried out on Google Sheets and for all data regarding payroll in the process of paying employee salaries via bank transfer. And the analysis of the company's Internal Control System has also been implemented in accordance with the policies set by the leadership.